Stability Enhancement by Zero‐Point Spin Fluctuations: A Quantum Perspective on Bloch Point Topological Singularities - Tapia, Alonso; Saji, Carlos; Roldán‐Molina, Alejandro; Nunez, Alvaro S. (Advanced functional materials, 2024)
Bloch points represent singularities within magnetic materials. From a macroscopic viewpoint, their cores are points where the magnetization vector is undefined, resulting in unique topological characteristics that influence the magnetic behavior of their hosts. The picture is very different at the microscopic level, where quantum effects enter the scene. The spin variables' quantum dynamics effect on the BP's stability is revealed. Zero‐point fluctuations, intrinsic fluctuations within the quantum mechanical ground state originating from the uncertainty principle, play a fundamental role. It is found that quantum fluctuations bloom in the vicinity of the singularity, thereby reducing the effective magnetic moment in its neighborhood. This increases the overall stability of the BP. These methods also allow for a characterization of the magnonic eigenmodes surrounding and bound to the singularity. The latter leads to predict on quite general grounds several features of the magnonic spectra, its degeneration structure, and its splitting response under a magnetic field. The last result is coherent with the association of a magnetic moment to the orbital angular momentum of the magnons. This approach allows integration with multiscale algorithms to provide a realistic description of generic topological singularities. Bloch points are singularities in magnetic materials with unique properties that affect their hosts' magnetic behavior. Quantum dynamics are crucial to their stability at the microscopic level. Zero‐point fluctuations reduce the effective magnetic moment near the singularity, enhancing stability. The methods also characterize magnonic eigenmodes associated with the singularity, predicting features of the spectra and their response to magnetic fields.